Clinical profile and visual outcome following pars plana vitrectomy in acute post-operative endophthalmitis - Thapa, R; Paudyal, G (Nepalese Journal of Ophthalmology, 2011)
Introduction: Endophthalmitis following cataract surgery is a rare but devastating ocular complication where delay in treatment not only results in vision loss but also in difficulty to save the eye ball. Objective: To explore the clinical profile and visual outcome following pars plana vitrectomy (PPV) in acute endophthalmitis after cataract surgery. Materials and methods: This is a retrospective interventional case series study conducted at Tilganga Institute of Ophthalmology (TIO), Nepal. All consecutive cases of acute endophthalmitis following cataract surgery treated with PPV from January 2005 to August 2010 were included in the study. Results: There were a total of 34 cases (34 eyes) treated with PPV. The age range was 8 - 93 years with mean age of 56.9 ± 19.5 years. The mean duration of presentation and duration following cataract surgery was 7.7 ± 8.1days and 13 ± 11.6 days respectively. Small incision cataract surgery was done in 75 % of cases followed by phacoemulsification (15.6 %). The mean duration of the last follow -up was 4.3 months. Vision was improved in two-thirds of cases (67.67 %) with a good vision of 6/18 or better in 17.6 %. Among the available vitreous samples of 22 cases, 36.36 % had an abnormality in Gram and Giemsa stains and culture was positive in 13.6 % of cases. Conclusion: Despite the late presentation, the majority of eyes were salvaged with improvement of vision in 67.67 %, with a good vision of 6/18 or better in 17.6 4 % of cases following PPV in acute post operative endophthalmitis. Key words: Endophthalmitis, vitrectomy, cataract surgery, visual outcome DOI: http://dx.doi.org/10.3126/nepjoph.v3i2.5260 Nepal J Ophthalmol 2011; 3(2): 102-108